Impact of Tax Knowledge, Tax Penalties, and E-Filing on Tax Compliance in India - Kushwah, Silky Vigg; Nathani, Navita; Vigg, Manav (Indian Journal of Finance, 2021)
This study investigated the tax compliance behaviour of corporate taxpayers in India. Based on the existing literature, three determinants were employed to study the tax compliance behaviour : tax knowledge, tax penalties, and electronic filing. To examine the impact of these independent determinants on compliance (dependent variable) by taxpayers, we collected survey data from 247 corporate taxpayers with a net worth less than ` 100 crores in Delhi and NCR in India during the period from January â€“ July 2019. Cronbach’s alpha test and one - sample Kolmogorov â€“ Smirnov test were used to check the reliability and normality of the data set, and a linear multiple regression model was used to test the hypotheses and check the relationship. The findings confirmed that tax penalties and electronic filing had a statistically significant influence on the corporate taxpayersâ€™ tax compliance, while tax knowledge did not show a statistically significant relation with tax compliance. The results could provide insights into progressive tax policy tools and administration strategies to augment taxpayer compliance, which will increase the nationâ€™s tax revenues. Further studies can be undertaken to understand the relationship of tax compliance with other determinants.